Iron monatomic / zinc atom cluster-nitrogen-carbon composite material as well as preparation method and application thereof

The iron single atom/zinc atom cluster-nitrogen-carbon composite material was prepared by room temperature stirring and thermal shock technology, which solved the problem of slow kinetics and insufficient stability of Fe-N-C catalysts in the oxygen reduction reaction, and achieved efficient catalytic activity and stability improvement, and was suitable for the cathode of zinc-air battery.

CN120545387APending Publication Date: 2025-08-26JILIN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510648612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing Fe-N-C catalysts have slow kinetics and insufficient stability in oxygen reduction reactions. The traditional synthesis methods are inefficient and difficult to achieve large-scale production.

Method used

The iron single atom/zinc atomic cluster-nitrogen-carbon composite material was prepared by room temperature stirring and thermal shock technology. The ZIF structure collapsed through rapid thermal shock, forming a Zn atomic cluster closely bound to the Fe-N4 site, achieving large-scale rapid preparation.

Benefits of technology

The catalytic activity and stability were significantly improved, and the catalytic activity and zinc-air battery performance were better than that of commercial Pt/C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120545387A_ABST
    Figure CN120545387A_ABST
Patent Text Reader

Abstract

The invention relates to an iron single atom / zinc atom cluster-nitrogen-carbon composite material as well as a preparation method and application thereof. Zinc nitrate hexahydrate, ferric acetylacetonate and dimethylimidazole are used as raw materials, and the iron single atom / zinc atom cluster-nitrogen-carbon composite material FeSA / ZnAC-N-C is prepared through stirring and thermal shock at room temperature. The preparation method comprises the following steps: a, stirring at room temperature to prepare an iron-zinc bimetallic zeolite imidazole organic framework FeZn-ZIF precursor; and b, carrying out thermal shock on the precursor to prepare the FeSA / ZnAC-N-C. The FeSA / ZnAC-N-C shows excellent oxygen reduction reaction (ORR) catalytic performance, the half-wave potential is 0.90 V, the Tafel slope is 46.4 mV dec-1, and the performance exceeds that of commercial Pt / C. Besides, the zinc-air battery constructed by taking FeSA / ZnAC-N-C as the air cathode can reach the maximum power density of 161.5 mW cm <-2 > and the specific discharge capacity of 792.7 mAh g <-1 >, can stably circulate for 1500 circles, and shows good practical application value. The preparation method can be expanded to preparation of other monatomic / atomic cluster composite materials, and a new idea is provided for development of efficient electrocatalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to an iron single atom / zinc atom cluster-nitrogen-carbon composite material and a preparation method and application thereof. Background Art

[0002] Zinc-air batteries have high energy density and conversion efficiency, are safe and environmentally friendly, and are expected to alleviate the increasingly severe energy crisis and environmental pollution problems. During the discharge process, the oxygen reduction reaction occurring at the cathode involves multi-electron transfer and the breaking of strong O-O bonds, and the kinetics are very slow, which greatly limits the actual working efficiency of the battery. Single-atom catalysts have the advantages of nearly 100% atomic utilization, uniform and clear active sites, and strong interactions between metals and supports, making them very promising oxygen reduction reaction catalytic materials. In particular, the active center is Fe-N x The Fe-NC single-atom catalyst with a relatively good oxygen reduction activity has attracted extensive attention from researchers. x The adsorption of oxygen-containing intermediates on the sites is too strong, and the Fenton reaction will inevitably occur during the electrochemical process. The above factors make it particularly difficult to further improve the intrinsic activity and stability of Fe-NC catalysts. Atomic clusters are usually composed of several to dozens of atoms, with unique electronic properties and geometric structures. x The combination of atomic clusters and Fe-NC sites is expected to improve the intrinsic catalytic activity and stability of Fe-NC materials. x The sites are far apart, which reduces their interaction. Furthermore, single-atom / atom cluster composites are typically synthesized using the traditional tube furnace pyrolysis method, which is time-consuming and inefficient, making it difficult to achieve rapid, large-scale production.

[0003] In response to the above problems, the present invention combines room temperature stirring and thermal shock technology to design and prepare a single iron atom / zinc atom cluster-nitrogen-carbon composite material. The extremely fast heating rate during the thermal shock process can cause the zeolite imidazole organic framework (ZIF) structure to collapse instantly, and the Zn atoms with a higher content aggregate into Zn atom clusters, while the Fe atoms with a lower content are captured by the N atoms in the carbon skeleton to form Fe-N4 sites. The thermal shock process only takes 90 seconds, which is conducive to the large-scale and rapid preparation of single-atom / atom cluster composite materials. More importantly, most of the Zn atom clusters in the composite material are surrounded by three Fe-N4 sites, two of which are very close to them (<0.3nm) and the other is farther away. On the one hand, the strong electronic interaction between the Zn atom clusters and the Fe-N4 sites can accelerate the electrochemical reaction rate and reduce the reaction energy barrier, thereby significantly improving the intrinsic catalytic activity; on the other hand, the Zn atom clusters and the very close Fe-N4 sites can stabilize each other, thereby greatly improving the overall stability of the composite material. Summary of the Invention

[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present disclosure provides an iron single atom / zinc atom cluster-nitrogen-carbon composite material and a preparation method and application thereof.

[0005] According to a first aspect of the present disclosure, a method for preparing an iron single atom / zinc atom cluster-nitrogen-carbon composite material is provided, characterized in that it comprises the following steps:

[0006] a. Preparation of FeZn-ZIF precursor at room temperature: 1-3 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.05-0.15 g iron acetylacetonate C 15 H 21 FeO6 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution A. 3-4 g of dimethylimidazole C4H6N2 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 20-30 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor.

[0007] b. Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: FeZn-ZIF precursor powder was placed in carbon cloth, and then the carbon cloth was fixed on a copper fixture and placed in a Joule thermal shock device filled with argon for thermal shock treatment. After cooling, the iron single atom / zinc atom cluster-nitrogen-carbon composite material Fe was obtained. SA / Zn AC -NC.

[0008] Preferably, the step b, preparing the iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock, is specifically as follows: 40-60 mg of FeZn-ZIF precursor powder is placed on an area of ​​10-12 cm 2 In the carbon cloth, the thermal shock voltage is set to 30~34V, the thermal shock current is set to 20~30A, and the thermal shock time is set to 80~100s.

[0009] According to a second aspect of the present disclosure, a single iron atom / zinc atom cluster-nitrogen-carbon composite material is provided.

[0010] According to a third aspect of the present disclosure, an application of an iron single atom / zinc atom cluster-nitrogen-carbon composite material is provided, and the composite material is used as a working electrode for electrochemical testing.

[0011] Preferably, the steps include:

[0012] a. First, 4-6 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 0.8-1.2 mL of water, isopropanol or naphthol solution and ultrasonicated for 40-60 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 10-20 μL of the Fe SA / Zn AC -NC catalyst ink solution was dropped onto the glassy carbon electrode and dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -Glass carbon electrode with NC catalyst film;

[0013] b. Electrochemical testing was performed in a standard three-electrode test system, where the Fe-coated prepared in step a SA / Zn AC -NC catalyst film glassy carbon electrode as the working electrode, carbon rod electrode as the counter electrode, silver / silver chloride electrode as the reference electrode, oxygen O2 saturated potassium hydroxide KOH solution with a concentration of 0.05-0.15M as the electrolyte;

[0014] c. Covered with Fe SA / Zn AC The glassy carbon electrode of the NC catalyst film was used as the working electrode for testing on an Ivium-n-Stat electrochemical workstation. During the cyclic voltammetry test, the potential scan range relative to the reversible hydrogen electrode was 0.2–1.1 V, and the scan rate was 50 mV s-1 Polarization curves were measured on a rotating disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3–1.1 V relative to the reversible hydrogen electrode and a scan rate of 10 mV s -1 The hydrogen peroxide yield and transferred electron number tests were carried out on a rotating ring disk electrode with a rotation speed of 1600 rpm, the potential scan range relative to the reversible hydrogen electrode was 0.3-1.1 V, and the applied ring voltage was 1.5 V; the methanol tolerance test was carried out at a potential of 0.7 V relative to the reversible hydrogen electrode and lasted for 600 s; the chronoamperometric test was carried out at a potential of 0.7 V relative to the reversible hydrogen electrode and lasted for 30 h.

[0015] According to a fourth aspect of the present disclosure, an application of an iron single atom / zinc atom cluster-nitrogen-carbon composite material is provided, and the iron single atom / zinc atom cluster-nitrogen-carbon composite material is used as an air cathode to perform zinc-air battery testing.

[0016] Preferably, the steps include:

[0017] a. First, 9-11 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 0.8-1.2 mL ethanol or naphthol solution and ultrasonicated for 40-60 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 90-110 μL of the Fe SA / Zn AC -NC catalyst ink solution is dropped onto carbon paper, hydrophobic layer or nickel foam composite electrode, with an effective area of ​​0.5 to 1.5 cm 2 , dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -NC catalyst film composite electrode;

[0018] b. The performance test of zinc-air battery was carried out in a standard two-electrode test system, wherein the Fe-coated prepared in step a SA / Zn AC The composite electrode of the -NC catalyst film is used as the cathode, the 0.4-0.6mm zinc sheet is used as the anode, and the mixed solution of potassium hydroxide KOH with a concentration of 5-7M and zinc acetate Zn(CH3COO)2 with a concentration of 0.1-0.3M is used as the electrolyte;

[0019] c. The composite electrode was used as a working electrode to perform a test on an Ivium-n-Stat electrochemical workstation. During the polarization curve test, the potential scan range relative to the reversible hydrogen electrode was 0.2-1.5 V, and the scan rate was 5 mV s -1 ; During the rate curve test, the discharge current density is from 2mA cm -2 At the beginning, 5mA cm -2 、10mA cm -2 , 25mA cm -2 、50mAcm -2 , and finally return to 2mA cm -2 The duration of each current density is 20 min; the discharge curve test is carried out at a current density of 10 mA cm -2 The cycling stability test was carried out at a current density of 5 mA cm -2 The charging and discharging time is 10 minutes, one cycle of charging and discharging is 20 minutes, and it lasts for 1500 cycles.

[0020] The purpose of the present invention is to provide an iron single atom / zinc atom cluster-nitrogen-carbon composite material and its preparation method and application. The composite material is prepared by combining room temperature stirring and thermal shock technology, showing uniformly distributed Zn atom clusters and single Fe atoms in close proximity to them, providing a large number of active sites for electrochemical reactions. At the same time, the strong interaction between the Zn atom clusters and single Fe atoms in the composite material not only accelerates the electrochemical reaction rate and reduces the reaction energy barrier, greatly improving its intrinsic catalytic activity, but also enhancing the overall stability of the composite material. In addition, the high-temperature thermal shock technology requires a short time, which can achieve efficient synthesis of single atom / atom cluster composite materials. The composite material has broad application prospects as an oxygen reduction catalyst and zinc-air battery cathode. The present invention can also be expanded to the design of other single atom / atom cluster composite materials, providing new ideas for the development of efficient electrocatalysts.

[0021] The technical effects of the present invention are:

[0022] In the iron single atom / zinc atom cluster-nitrogen-carbon composite material prepared by the present invention, the Zn atom clusters and Fe single atoms provide a large number of active sites for electrochemical reactions; at the same time, the strong interaction between the Zn atom clusters and the adjacent Fe single atom sites not only accelerates the electrochemical reaction rate and reduces the reaction energy barrier, greatly improving its intrinsic catalytic activity, but also enhances the overall stability of the composite material, thereby enabling the composite material to exhibit ORR catalytic activity and zinc-air battery performance exceeding that of commercial Pt / C. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1, polarization curves of different electrodes in Example 1 of the present invention.

[0024] Figure 2 , Fe prepared in Example 1 of the present invention SA / Zn AC -XRD pattern of NC.

[0025] Figure 3 , Fe prepared in Example 1 of the present invention SA / Zn AC -TEM image of NC.

[0026] Figure 4 , Fe prepared in Example 1 of the present invention SA / Zn AC -HRTEM image of NC.

[0027] Figure 5 , Fe prepared in Example 1 of the present invention SA / Zn AC -SAED photo of NC.

[0028] Figure 6 , Fe prepared in Example 1 of the present invention SA / Zn AC -TGA curve of NC.

[0029] Figure 7 , Fe prepared in Example 1 of the present invention SA / Zn AC -HAADF-STEM image of NC.

[0030] Figure 8 , Fe prepared in Example 1 of the present invention SA / Zn AC -Raman spectrum of NC.

[0031] Figure 9 , Fe prepared in Example 1 of the present invention SA / Zn AC -NC BET spectrum (the inset is Fe SA / Zn AC -NC pore size distribution diagram).

[0032] Figure 10 , Fe prepared in Example 1 of the present invention SA / Zn AC -XPS full spectrum of NC.

[0033] Figure 11 , Fe prepared in Example 1 of the present invention SA / Zn AC-High-resolution XPS spectrum of the N1s region of NC.

[0034] Figure 12 , Fe prepared in Example 1 of the present invention SA / Zn AC Fe K-edge XANES spectra of -NC and standard samples.

[0035] Figure 13 , Fe prepared in Example 1 of the present invention SA / Zn AC Fe K-edge FT-EXAFS spectra of -NC and standard samples.

[0036] Figure 14 , Fe prepared in Example 1 of the present invention SA / Zn AC Fitting curve of the Fe K-edge FT-EXAFS spectrum of -NC.

[0037] Figure 15 , Fe prepared in Example 1 of the present invention SA / Zn AC High-resolution XPS spectrum of the Zn 2p region of -NC.

[0038] Figure 16 , Fe prepared in Example 1 of the present invention SA / Zn AC High-resolution XPS spectrum of the Zn LMM region of -NC.

[0039] Figure 17 , Fe prepared in Example 1 of the present invention SA / Zn AC Zn K-edge XANES spectra of -NC and standard samples.

[0040] Figure 18 , Fe prepared in Example 1 of the present invention SA / Zn AC Zn K-edge FT-EXAFS spectra of -NC and standard samples.

[0041] Figure 19 , Fe prepared in Example 1 of the present invention SA / Zn AC Fitting curve of the Zn K-edge FT-EXAFS spectrum of -NC.

[0042] Figure 20 , Cyclic voltammetry curves of different electrodes in Example 1 of the present invention.

[0043] Figure 21 , kinetic current density curves of different electrodes in Example 1 of the present invention.

[0044] Figure 22 , Tafel curves of different electrodes in Example 1 of the present invention.

[0045] Figure 23 , Fe prepared in Example 1 of the present invention SA / Zn AC Electron transfer number and hydrogen peroxide yield curves of Pt-NC and commercial Pt / C.

[0046] Figure 24 , Fe prepared in Example 1 of the present invention SA / Zn AC Methanol tolerance curves of NC and commercial Pt / C.

[0047] Figure 25 , Fe prepared in Example 1 of the present invention SA / Zn AC -Chronoamperometric curves of NC and commercial Pt / C.

[0048] Figure 26 , Fe prepared in Example 1 of the present invention SA / Zn AC -TEM image of NC after chronoamperometry test.

[0049] Figure 27 , Fe prepared in Example 1 of the present invention SA / Zn AC -Open-circuit voltage curves of NC and commercial Pt / C zinc-air batteries.

[0050] Figure 28 , Fe prepared in Example 1 of the present invention SA / Zn AC Discharge polarization curves of NC and commercial Pt / C zinc-air batteries.

[0051] Figure 29 , Fe prepared in Example 1 of the present invention SA / Zn AC Rate curves of NC and commercial Pt / C zinc-air batteries.

[0052] Figure 30 , Fe prepared in Example 1 of the present invention SA / Zn AC Constant-galvanostatic discharge curves of NC and commercial Pt / C zinc-air batteries.

[0053] Figure 31 , Fe prepared in Example 1 of the present invention SA / Zn AC Cycling stability curves of NC and commercial Pt / C zinc-air batteries.

[0054] Figure 32 , Fe prepared in Example 2 of the present invention SA / Zn AC -TEM image of NC.

[0055] Figure 33 , Fe prepared in Example 3 of the present invention SA / Zn AC -TEM image of NC. DETAILED DESCRIPTION

[0056] To make the purpose, technical solutions, and advantages of the embodiments of the present disclosure more clear, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present disclosure.

[0057] The present invention provides a method for preparing an iron single atom / zinc atom cluster-nitrogen-carbon composite material, which is characterized by comprising the following steps:

[0058] a. Preparation of FeZn-ZIF precursor at room temperature: 1-3 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.05-0.15 g iron acetylacetonate C 15 H 21 FeO6 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution A. 3-4 g of dimethylimidazole C4H6N2 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 20-30 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor.

[0059] b. Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: FeZn-ZIF precursor powder was placed in carbon cloth, and then the carbon cloth was fixed on a copper fixture and placed in a Joule thermal shock device filled with argon for thermal shock treatment. After cooling, the iron single atom / zinc atom cluster-nitrogen-carbon composite material Fe was obtained. SA / Zn AC -NC.

[0060] The contents of Examples 2 and 3 of the present invention are similar to those of Example 1, and will now be described in detail taking Example 1 as an example.

[0061] Example 1

[0062] The preparation process and steps in Example 1 are as follows:

[0063] (1) Preparation of FeZn-ZIF precursor by stirring at room temperature: 1.72 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.10 g iron acetylacetonate C 15 H 21 FeO6 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution A. 3.70 g of dimethylimidazole C4H6N2 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 24 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor.

[0064] (2) Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: 50 mg of FeZn-ZIF precursor powder was placed on an area of ​​11 cm 2 The carbon cloth was then fixed on a copper fixture and placed in a Joule thermal shock device filled with argon. The thermal shock voltage was set to 32 V, the thermal shock current was set to 25 A, and the thermal shock time was set to 90 s. After cooling, it was converted into an iron single atom / zinc atom cluster-nitrogen-carbon composite material Fe SA / Zn AC -NC;

[0065] (3) First, 5 mg Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of water, isopropanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then 16 μL Fe SA / Zn AC -NC catalyst ink solution was dropped onto the glassy carbon electrode and dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering single iron atoms / zinc atom clusters-nitrogen-carbon Fe SA / Zn AC -Glass carbon electrode with NC catalyst film;

[0066] (4) Covered with the iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn ACThe glassy carbon electrode of the NC catalyst film was used as the working electrode for testing on an Ivium-n-Stat electrochemical workstation. During the cyclic voltammetry test, the potential scan range relative to the reversible hydrogen electrode was 0.2–1.1 V, and the scan rate was 50 mV s -1 Polarization curves were measured on a rotating disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3–1.1 V relative to the reversible hydrogen electrode and a scan rate of 10 mV s -1 The hydrogen peroxide yield and transferred electron number tests were conducted on a rotating ring disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3 to 1.1 V relative to the reversible hydrogen electrode and an applied ring voltage of 1.5 V. The methanol tolerance test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 600 s. The chronoamperometric test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 30 h.

[0067] (5) First, 10 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of ethanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 100 μL and drop it on carbon paper, hydrophobic layer or nickel foam composite electrode, with an effective area of ​​1 cm 2 , dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -NC catalyst film composite electrode;

[0068] (6) The composite electrode was used as a working electrode to conduct a test on an Ivium-n-Stat electrochemical workstation: during the polarization curve test, the potential scanning range relative to the reversible hydrogen electrode was 0.2-1.5 V, and the scanning rate was 5 mV s -1 ; During the rate curve test, the discharge current density is from 2mA cm -2 At the beginning, 5mA cm -2 、10mA cm -2 , 25mA cm -2 、50mAcm -2 , and finally return to 2mA cm -2 The duration of each current density is 20 min; the discharge curve test is carried out at a current density of 10 mA cm -2 The cycling stability test was carried out at a current density of 5 mA cm-2 The charging and discharging time is 10 minutes, one cycle of charging and discharging is 20 minutes, and it lasts for 1500 cycles.

[0069] Fe SA / Zn AC -NC morphology and structure characterization:

[0070] Figure 2 Fe SA / Zn AC -NC X-ray diffraction (XRD) spectrum, the diffraction peaks at 24.7° and 44.3° correspond to the (002) and (101) crystal planes of amorphous carbon, respectively, which indicates that Fe SA / Zn AC -No large metal particles are present in NC. Figure 3 Fe SA / Zn AC Transmission electron microscopy (TEM) images of -NC show irregular polyhedrons. This is because the extremely rapid heating rate during the thermal shock process instantly destroys the FeZn-ZIF structure, making it unable to maintain its original regular polyhedron morphology. Figure 4 Fe SA / Zn AC -High-resolution TEM (HRTEM) image of NC, in which no lattice fringes of the metallic phase were observed. Figure 5 Fe SA / Zn AC -NC selected area electron diffraction (SAED) pattern, in which only two broad diffraction rings corresponding to amorphous carbon can be observed, which is consistent with the XRD results. Figure 6 Fe SA / Zn AC -NC thermogravimetric (TGA) curve. It can be seen that after heating to 800 ° C in air, only a small amount of oxide (10.49%) remains. This indicates that Fe SA / Zn AC -NC contains less Fe and Zn elements. Combined with the above experimental results, Fe and Zn elements may exist in the form of ultra-small atomic clusters or single atoms. SA / Zn AC -NC. Fe was measured by inductively coupled plasma optical emission spectroscopy (ICP-OES) SA / Zn AC The contents of Fe and Zn in -NC are 0.22 and 7.14 wt%, respectively. Figure 7 Fe SA / Zn AC-NC high angle annular dark field scanning TEM (HAADF-STEM) image, in which a large number of single atomic sites (partly marked by small circles) and atomic clusters (partly marked by large circles) can be observed. Combined with the ICP-OES results, it can be seen that Fe SA / Zn AC Fe and Zn in -NC tend to exist as single atoms and clusters, respectively. Notably, most Zn clusters are surrounded by three Fe single-atom sites (partially marked by dashed boxes), two of which are very close to the Zn cluster (<0.3 nm), while the other is farther away. This unique structure enhances the electronic interaction between the Fe single-atom sites and the Zn cluster, which is beneficial for improving the intrinsic catalytic activity and overall stability of the material. Figure 8 Fe SA / Zn AC -NC Raman spectrum, the calculated intensity ratio of the D band to the G band is 1.06, indicating that its defect level is high. Figure 9 Fe SA / Zn AC The N2 adsorption / desorption curves and pore size distribution curves of -NC (inset). The Fe SA / Zn AC The specific surface area and total pore volume of -NC are 564.19 m 2 / g and 0.40cm 3 / g. A higher degree of defects, a larger specific surface area, and a rich pore structure can accelerate the electrochemical reaction rate, thereby increasing Fe SA / Zn AC -NC catalytic activity. Figure 10 Fe SA / Zn AC -NC X-ray photoelectron spectroscopy (XPS) full spectrum, in which signals of Zn, C, N, and O can be detected. The Fe element signal is absent in the XPS full spectrum, which is due to its low content. Figure 11 Fe SA / Zn AC -NC N1s high-resolution XPS spectrum can be fitted with Pyridinic-N, Pyrrolic-N, Graphitic-N, Oxidized-N and Fe-N characteristic peaks. The appearance of Fe-N characteristic peaks indicates that Fe SA / Zn AC There is coordination between Fe and N atoms in -NC. Figure 12 FeSA / Zn AC Fe K-edge X-ray absorption near-edge structure (XANES) spectra of -NC and standard samples. It can be seen that Fe SA / Zn AC The absorption edge energy of -NC is much higher than that of Fe foil and is located between Fe3O4 and Fe2O3 (inset). SA / Zn AC The valence state of Fe in -NC is between +2 and +3. Figure 13 Fe SA / Zn AC -NC and standard samples of Fe K-edge Fourier transform extended X-ray absorption structure (FT-EXAFS) spectra, which are The Fe-N characteristic peak was observed at SA / Zn AC -NC formed Fe-N coordination, which is consistent with the XPS results. In addition, the FT-EXAFS spectrum can be observed at The Fe-Zn characteristic peaks indicate that the Fe single atom site is very close to the Zn atomic cluster, and the distance between them is less than 0.3 nm, which is consistent with the HAADF-STEM analysis. Figure 14 Fe SA / Zn AC -NC Fe K-edge FT-EXAFS spectrum fitting curve. The best fitting result shows that Fe SA / Zn AC The numbers of N and Zn atoms coordinated with Fe in -NC are 3.5 and 1.2, respectively, indicating that Fe is coordinated with four N atoms in the first shell, forming Fe-N4 active sites. Figure 15 Fe SA / Zn AC The high-resolution XPS spectrum of Zn 2p of -NC can be fitted to the Zn 2+ 2p 3 / 2 and Zn 2+ 2p 1 / 2 Characteristic peak. Figure 16 Fe SA / Zn AC -NC Zn LMM high-resolution XPS spectrum, in which the Auger peak of Zn can be observed at 988.3eV. The above results all indicate that Fe SA / Zn AC The valence state of Zn in -NC is very close to +2. Figure 17 Fe SA / Zn AC -NC and standard sample Zn K-edge XANES spectra, where FeSA / Zn AC The absorption edge of -NC almost coincides with the absorption edge of ZnO, indicating that Fe SA / Zn AC The valence state of Zn in -NC is approximately +2, consistent with the XPS results. This phenomenon is caused by the inevitable oxidation of the sample when exposed to air. Figure 18 Fe SA / Zn AC -NC and standard samples of Zn K-edge FT-EXAFS spectra, which can be found at 1.7 and The Zn-O and Zn-Zn / Fe characteristic peaks are observed at SA / Zn AC The Zn in -NC is oxidized in the air, thereby forming a large amount of Zn-O coordination. Figure 19 Fe SA / Zn AC -NC ZnK edge FT-EXAFS spectrum fitting curve. The results show that Fe SA / Zn AC The ratio of Zn / Fe atoms coordinated with Zn in α-NC is 1.1, which is completely different from the coordination number of Zn in Zn foil and ZnO, further confirming the formation of partially oxidized Zn atomic clusters.

[0071] At room temperature, Fe SA / Zn AC Characterization of catalytic performance of -NC:

[0072] Electrochemical experiments were performed using a standard three-electrode test system. Figure 20 For different electrodes at 50mV s -1 Cyclic voltammetry curves at scan rates. In an O2-saturated electrolyte (solid line), Fe SA / Zn AC -NC、Fe SA -NC、Zn AC -NC and commercial Pt / C both showed obvious reduction peaks. In N2 saturated electrolyte (dashed line), the above reduction peaks disappeared, indicating that all four materials have certain ORR activity. SA / Zn AC -NC's reduction peak is located at 0.82 V, which is superior to Fe SA -NC(0.75V), Zn AC -NC (0.68 V) and commercial Pt / C (0.81 V), indicating that it has the best ORR performance. Figure 1 For different electrodes at 10mV s -1 Polarization curves at different scanning rates. In alkaline environment, FeSA / Zn AC -NC half-wave potential (E 1 / 2 ) and limiting current density (j L ) are 0.90 V and 5.68 mA cm -2 , significantly better than Fe SA -NC(E 1 / 2 =0.83V and j L =5.28mAcm -2 ), Zn AC -NC(E 1 / 2 =0.76V and j L =3.62mAcm -2 ) and commercial Pt / C(E 1 / 2 =0.86V and j L =5.37mAcm -2 ). Figure 21 The kinetic current density curves of different electrodes. At 0.9V, Fe SA / Zn AC The kinetic current density of NC is 3.98 mA cm -2 , respectively commercial Pt / C, Fe SA -NC and Zn AC -NC, which were 1.9, 6.1 and 14.2 times that of -NC, indicating that its reaction kinetics were the fastest. Figure 22 is the Tafel curve of different electrodes, Fe SA / Zn AC -NC、Fe SA -NC、Zn AC The Tafel slopes of NC and commercial Pt / C are 46.4, 92.1, 102.8, and 80.0 mV dec, respectively. -1 .Fe SA / Zn AC -NC has the smallest Tafel slope, indicating that it has the fastest reaction kinetics, which is consistent with the kinetic current density results. Figure 23 Fe SA / Zn AC The transfer electron number and hydrogen peroxide yield curves of -NC and commercial Pt / C. In the potential range of 0.4~0.8V, Fe SA / Zn AC The number of transferred electrons and the hydrogen peroxide yield of -NC were 3.7 and 7.3%, respectively, indicating its high electrochemical selectivity. Figure 24 Fe SA / Zn AC Methanol tolerance curves of -NC and commercial Pt / C. After adding 15 mL of methanol solution to the electrolyte at 300 s, Fe SA / Zn AC -NC has a small current fluctuation and can return to the current level before the addition of methanol within a few seconds, indicating its excellent methanol tolerance. Figure 25 Fe SA / Zn AC -NC and commercial Pt / C chronoamperometric curves, at a potential of 0.7 V, after 30 h of continuous testing, Fe SA / Zn AC -NC has almost no obvious current decay, while the current decay of commercial Pt / C has reached 10.1% after 4.5h testing. This result shows that compared with commercial Pt / C, Fe SA / Zn AC -NC has better electrochemical stability. Figure 26 Fe SA / Zn AC - TEM photo of NC after 30h chronoamperometric test, Fe SA / Zn AC -NC still maintains an irregular polyhedral morphology, similar to that before the stability test, indicating that it has good structural stability.

[0073] At room temperature, Fe SA / Zn AC -NC zinc-air battery performance characterization:

[0074] The electrochemical experiments were carried out using a two-electrode test system. Figure 27 Fe SA / Zn AC Open circuit voltage curves of NC and commercial Pt / C zinc-air batteries. SA / Zn AC The open circuit voltage of the -NC zinc-air battery is 1.48 V, which is higher than that of the commercial Pt / C zinc-air battery (1.45 V), indicating that it has better electrochemical performance. Figure 28 Fe SA / Zn AC Discharge polarization curves of NC and commercial Pt / C zinc-air batteries, where Fe SA / Zn AC The maximum power density of the NC zinc-air battery can reach 161.5 mW cm -2 , which is superior to commercial Pt / C zinc-air batteries (115.2 mW cm -2 ), further confirmed that Fe SA / Zn AC -NC has better ORR activity. Figure 29 Fe SA / Zn AC-NC and commercial Pt / C zinc-air battery discharge curves at different current densities. It can be seen that compared with commercial Pt / C zinc-air battery, Fe SA / Zn AC The discharge voltage of the NC zinc-air battery at each current density is higher and more stable. -2 When Fe SA / Zn AC The voltage retention of the NC zinc-air battery is approximately 99.6%, which is better than that of the commercial Pt / C zinc-air battery (98.4%), indicating its excellent rate capability. Figure 30 Fe SA / Zn AC -NC and commercial Pt / C zinc-air batteries at a current density of 10 mA cm -2 The constant current discharge curve of Fe SA / Zn AC The discharge specific capacities of the NC and commercial Pt / C zinc-air batteries are 792.7 and 751.6 mAh g, respectively. -1 .Fe SA / Zn AC -NC zinc-air battery has a higher discharge specific capacity, indicating its better electrochemical performance. Figure 31 Fe SA / Zn AC Cycling stability curves of NC and commercial Pt / C zinc-air batteries at 5 mA cm -2 At the charge and discharge current density of Fe SA / Zn AC -NC zinc-air battery can be cycled stably for 1500 cycles, while commercial Pt / C zinc-air battery can only cycle 420 cycles. SA / Zn AC -NC zinc-air batteries have good cycling stability.

[0075] Example 2

[0076] The preparation process and steps in Example 2 are as follows:

[0077] (1) Preparation of FeZn-ZIF precursor by stirring at room temperature: 1.65 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.20 g iron acetylacetonate C 15 H 21FeO6 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution A. 3.70 g of dimethylimidazole C4H6N2 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 24 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor.

[0078] (2) Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: 50 mg of FeZn-ZIF precursor powder was placed on an area of ​​11 cm 2 The carbon cloth was then fixed on a copper fixture and placed in a Joule thermal shock device filled with argon. The thermal shock voltage was set to 32V, the thermal shock current was set to 25A, and the thermal shock time was set to 90s. After cooling, it was converted into iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC;

[0079] (3) First, 5 mg of single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of water, isopropanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 16 μL of the Fe SA / Zn AC -NC catalyst ink solution was dropped onto the glassy carbon electrode and dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -Glass carbon electrode with NC catalyst film;

[0080] (4) Covered with the single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC The glassy carbon electrode of the NC catalyst film was used as the working electrode for testing on an Ivium-n-Stat electrochemical workstation. During the cyclic voltammetry test, the potential scan range relative to the reversible hydrogen electrode was 0.2–1.1 V, and the scan rate was 50 mV s -1 Polarization curves were measured on a rotating disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3–1.1 V relative to the reversible hydrogen electrode and a scan rate of 10 mV s -1The hydrogen peroxide yield and transferred electron number tests were conducted on a rotating ring disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3 to 1.1 V relative to the reversible hydrogen electrode and an applied ring voltage of 1.5 V. The methanol tolerance test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 600 s. The chronoamperometric test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 30 h.

[0081] (5) First, 10 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of ethanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 100 μL of the Fe SA / Zn AC -NC catalyst ink solution was dropped onto carbon paper, hydrophobic layer or nickel foam composite electrode with an effective area of ​​1cm 2 , dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -NC catalyst film composite electrode;

[0082] (6) The composite electrode was used as a working electrode to conduct a test on an Ivium-n-Stat electrochemical workstation: during the polarization curve test, the potential scanning range relative to the reversible hydrogen electrode was 0.2-1.5 V, and the scanning rate was 5 mV s -1 ; When the rate curve is tested, the discharge current density is from 2mAcm -2 At the beginning, 5mA cm -2 、10mAcm -2 , 25mAcm -2 , 50mA cm -2 , and finally return to 2mA cm -2 The duration of each current density is 20min; the discharge curve test is carried out at a current density of 10mAcm -2 The cycle stability test was carried out at a current density of 5 mA cm -2 The charging and discharging time is 10 minutes, one cycle of charging and discharging is 20 minutes, and it lasts for 1500 cycles.

[0083] The Fe SA / Zn AC -TEM images of NC are shown in Figure 32As shown in the figure, it can be seen that the composite material prepared in Example 2 has a similar irregular polyhedron morphology to the material prepared in Example 1.

[0084] Example 3

[0085] The preparation process and steps in Example 3 are as follows:

[0086] (1) Stirring the FeZn-ZIF precursor at room temperature: 1.75 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.07 g iron acetylacetonate C 15 H 21 FeO6 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution A. 3.70 g of dimethylimidazole C4H6N2 was dissolved in 80 mL of methanol solution and stirred with a magnetic stirrer for 8 minutes. The resulting clear solution was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 24 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor.

[0087] (2) Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: 50 mg of FeZn-ZIF precursor powder was placed on an area of ​​11 cm 2 The carbon cloth was then fixed on a copper fixture and placed in a Joule thermal shock device filled with argon. The thermal shock voltage was set to 32V, the thermal shock current was set to 25A, and the thermal shock time was set to 90s. After cooling, it was converted into iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC;

[0088] (3) First, 5 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of water, isopropanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 16 μL of the Fe SA / Zn AC -NC catalyst ink solution was dropped onto the glassy carbon electrode and dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -Glass carbon electrode with NC catalyst film;

[0089] (4) Covered with the iron single atom / zinc atom cluster-nitrogen-carbon FeSA / Zn AC The glassy carbon electrode of the NC catalyst film was used as the working electrode for testing on an Ivium-n-Stat electrochemical workstation. During the cyclic voltammetry test, the potential scan range relative to the reversible hydrogen electrode was 0.2–1.1 V, and the scan rate was 50 mV s -1 Polarization curves were measured on a rotating disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3–1.1 V relative to the reversible hydrogen electrode and a scan rate of 10 mV s -1 The hydrogen peroxide yield and transferred electron number tests were conducted on a rotating ring disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3 to 1.1 V relative to the reversible hydrogen electrode and an applied ring voltage of 1.5 V. The methanol tolerance test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 600 s. The chronoamperometric test was conducted at a potential of 0.7 V relative to the reversible hydrogen electrode for 30 h.

[0090] (5) First, 10 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 1 mL of ethanol or naphthol solution and ultrasonicated for 50 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 100 μL of the Fe SA / Zn AC -NC catalyst ink solution is dropped on carbon paper, hydrophobic layer or nickel foam composite electrode, with an effective area of ​​1cm 2 , dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -NC catalyst film composite electrode;

[0091] (6) The composite electrode was used as a working electrode to conduct a test on an Ivium-n-Stat electrochemical workstation: during the polarization curve test, the potential scanning range relative to the reversible hydrogen electrode was 0.2-1.5 V, and the scanning rate was 5 mV s -1 ; When the rate curve is tested, the discharge current density is from 2mAcm -2 At the beginning, 5mA cm -2 、10mA cm -2 , 25mA cm -2 、50mAcm -2 , and finally return to 2mA cm -2The duration of each current density is 20 min; the discharge curve test is carried out at a current density of 10 mA cm -2 The cycling stability test was carried out at a current density of 5 mA cm -2 The charging and discharging time is 10 minutes, one cycle of charging and discharging is 20 minutes, and it lasts for 1500 cycles.

[0092] The Fe SA / Zn AC -TEM images of NC are shown in Figure 33 As shown in the figure, it can be seen that the composite material prepared in this example has a similar irregular polyhedron morphology as the materials prepared in Example 1 and Example 2.

[0093] The above embodiment is only one embodiment of the present invention, not all, and cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an iron single atom / zinc atom cluster-nitrogen-carbon composite material, characterized in that: The following steps are involved: a. Preparation of FeZn-ZIF precursor at room temperature: 1-3 g zinc nitrate hexahydrate Zn(NO3)2·6H2O and 0.05-0.15 g iron acetylacetonate C 15 H 21 FeO6 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution A. 3-4 g of dimethylimidazole C4H6N2 was dissolved in 70-90 mL of methanol solution and stirred with a magnetic stirrer for 5-10 minutes to obtain a clear solution, which was recorded as solution B. Solution B was quickly poured into solution A, and the resulting mixed solution was stirred continuously at room temperature for 20-30 hours. It was then centrifuged, washed, and dried to obtain a light yellow powder, which was the FeZn-ZIF precursor. b. Preparation of iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock: FeZn-ZIF precursor powder was placed in carbon cloth, and then the carbon cloth was fixed on a copper fixture and placed in a Joule thermal shock device filled with argon for thermal shock treatment. After cooling, the iron single atom / zinc atom cluster-nitrogen-carbon composite material Fe was obtained. SA / Zn AC -NC.

2. The method for preparing the iron single atom / zinc atom cluster-nitrogen-carbon composite material according to claim 1, characterized in that: The step b, preparing the iron single atom / zinc atom cluster-nitrogen-carbon composite material by thermal shock, is specifically as follows: 40-60 mg of iron-zinc bimetallic zeolite imidazole organic framework FeZn-ZIF precursor powder is placed in an area of ​​10-12 cm 2 In the carbon cloth, the thermal shock voltage is set to 30~34V, the thermal shock current is set to 20~30A, and the thermal shock time is set to 80~100s.

3. An iron single atom / zinc atom cluster-nitrogen-carbon composite material obtained according to the preparation method according to any one of claims 1-2.

4. The use of the iron single atom / zinc atom cluster-nitrogen-carbon composite material according to claim 3, characterized in that: The iron single atom / zinc atom cluster-nitrogen-carbon composite material was used as a working electrode for electrochemical testing.

5. Use of the iron single atom / zinc atom cluster-nitrogen-carbon composite material according to claim 4, characterized in that: The following steps are involved: a. First, 4-6 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 0.8-1.2 mL of water, isopropanol or naphthol solution and ultrasonicated for 40-60 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 10-20 μL of the Fe SA / Zn AC -NC catalyst ink solution was dropped onto the glassy carbon electrode and dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -Glass carbon electrode with NC catalyst film; b. Electrochemical testing was performed in a standard three-electrode test system, where the Fe-coated prepared in step a SA / Zn AC -NC catalyst film glassy carbon electrode as the working electrode, carbon rod electrode as the counter electrode, silver / silver chloride electrode as the reference electrode, oxygen O2 saturated potassium hydroxide KOH solution with a concentration of 0.05-0.15M as the electrolyte; c. Covered with Fe SA / Zn AC The glassy carbon electrode of the NC catalyst film was used as the working electrode for testing on an Ivium-n-Stat electrochemical workstation. During the cyclic voltammetry test, the potential scan range relative to the reversible hydrogen electrode was 0.2–1.1 V, and the scan rate was 50 mV s -1 Polarization curves were measured on a rotating disk electrode at a rotation speed of 1600 rpm, with a potential scan range of 0.3–1.1 V relative to the reversible hydrogen electrode and a scan rate of 10 mV s -1 The hydrogen peroxide yield and transferred electron number tests were carried out on a rotating ring disk electrode with a rotation speed of 1600 rpm, the potential scan range relative to the reversible hydrogen electrode was 0.3-1.1 V, and the applied ring voltage was 1.5 V; the methanol tolerance test was carried out at a potential of 0.7 V relative to the reversible hydrogen electrode and lasted for 600 s; the chronoamperometric test was carried out at a potential of 0.7 V relative to the reversible hydrogen electrode and lasted for 30 h.

6. Use of the iron single atom / zinc atom cluster-nitrogen-carbon composite material according to claim 3, characterized in that: The iron single atom / zinc atom cluster-nitrogen-carbon composite material was used as an air cathode to carry out zinc-air battery testing.

7. Use of the iron single atom / zinc atom cluster-nitrogen-carbon composite material according to claim 6, characterized in that: The following steps are involved: a. First, 9-11 mg of iron single atom / zinc atom cluster-nitrogen-carbon Fe SA / Zn AC -NC catalyst was dispersed in 0.8-1.2 mL ethanol or naphthol solution and ultrasonicated for 40-60 min to obtain Fe SA / Zn AC -NC catalyst ink solution, and then take out 90-110 μL of the Fe SA / Zn AC -NC catalyst ink solution is dropped onto carbon paper, hydrophobic layer or nickel foam composite electrode, with an effective area of ​​0.5 to 1.5 cm 2 , dried at room temperature to form a uniform Fe SA / Zn AC -NC catalyst film, obtained by covering Fe SA / Zn AC -NC catalyst film composite electrode; b. The performance test of zinc-air battery was carried out in a standard two-electrode test system, wherein the Fe-coated prepared in step a SA / Zn AC The composite electrode of the -NC catalyst film is used as the cathode, the 0.4-0.6mm zinc sheet is used as the anode, and the mixed solution of potassium hydroxide KOH with a concentration of 5-7M and zinc acetate Zn(CH3COO)2 with a concentration of 0.1-0.3M is used as the electrolyte; c. The composite electrode was used as a working electrode to perform a test on an Ivium-n-Stat electrochemical workstation. During the polarization curve test, the potential scan range relative to the reversible hydrogen electrode was 0.2-1.5 V, and the scan rate was 5 mV s -1 ; During the rate curve test, the discharge current density is from 2mA cm -2 At the beginning, 5mA cm -2 、10mA cm -2 , 25mA cm -2 , 50mA cm -2 , and finally return to 2mAcm -2 The duration of each current density is 20min; the discharge curve test is carried out at a current density of 10mAcm -2 The cycle stability test was carried out at a current density of 5 mA cm -2 The charging and discharging time is 10 minutes, one cycle of charging and discharging is 20 minutes, and it lasts for 1500 cycles.

Citation Information

Cited By

  • Preparation method and application of topological insulator composite catalytic material

    CN120878860A